Структурно-семантический анализ латинских паремий (на материале французских, испанских, русских текстов) - Науменко, Н.П.; Шибаева, И.В. (Культура народов Причерноморья, 2013)
В статье обращается внимание на латинскую паремиологию, которая является основным
источником французской, испанской паремиологии. Данная статья посвящена исследованию
латинских выражений. Пословицы даны с переводами на русский, французский, испанский языки. Цель
работы заключается в определении характерных особенностей выбранных нами выражений и в их
системном анализе.
Ключевые слова: паремиология, фразеология, семантический анализ. пословицы, поговорки, максимы,
афоризмы. В статті звертається увага на латинську пареміологію, як основне джерело французької,
іспанської пареміології. Дана стаття присвячена дослідженню латинських виразів. Прислів'я дани з
перекладами російською, французькою, іспанською мовами. Мета роботи полягає у визначенні
характерних особливостей обраних нами виразів та в системному аналізі.
Ключові слова: пареміологія, семантичий аналіз, прислів'я, приказки, максими, афоризмы. Proverbs, sayings, eloquent expressions, aphorisms, maxims, sententiosities of different peoples are
ideas of the world, perception of the environment by different cultures. Since ancient times in the speech usage
along with set expressions each people uses set phrases. The article is devoted to the research of the Latin
expressions written by great people: philosophers, thinker, writers, military leaders, etc. The proverbs are given
with the translations into the Russian, French, Spanish languages what stimulates the interest to studying the
languages on the whole. The usage of the set units is part and parcel of good command of the foreign languages.
The purpose of the research is in defining the peculiarities of the chosen expressions chosen by us, in the system
analysis and their usage in the belles-letters literature. The object of the research in the work is the Latin
expressions taken from the texts by the French, Spanish and Russian writers.
The subject of the research is the semantic analysis of the Latin expressions and their translations, defining their
semantic characteristics, analysis and generalization of the theoretical material on the problem of defining their
status in the modern linguistics, the sources of origin of the Latin expressions – looking for similarity and
difference in ther semantic aspect.
In the process of in the article one analyzes the notion of phraseology, paremiology, one makes the semantic
classification and typology of the Latin expressions.
Key words: paremiology, semantic analysis, proverbs, sayings, maxims, aphorisms.